Newly validated touch experiences and attitudes questionnaire in German (TEAQ-G) is linked to social functioning, mental health, and hormonal stress regulation - Schneider, Ekaterina; Raithel, Charlotte; Hopf, Dora; Scheele, Dirk; Trotter, Paula D.; Franz, Svea; Aguilar-Raab, Corina; Ditzen, Beate; Eckstein, Monika (Scientific reports, 2025)
Interpersonal affectionate touch plays a crucial role in social bonding, stress regulation, and psychological well-being. However, individual differences in past touch experiences and attitudes toward touch remain understudied. This study aimed to validate the German version of the touch experiences and attitudes questionnaire (TEAQ-G) and investigate how the subscales childhood touch experiences, current intimate touch, and attitudes toward touch relate to social relationships, mental health, emotional states, cortisol and oxytocin levels in everyday life. Data from 1,319 study participants suggest good psychometric properties of the TEAQ-G, confirming its reliability and validity as a tool for assessing touch experiences and attitudes. Regression analyses revealed that retrospectively reported more positive childhood touch and current intimate touch were associated with lower levels of attachment avoidance, stress, anxiety, depression, and loneliness, as well as higher resilience, family functioning, and relationship satisfaction. These findings were further supported by ecological momentary assessment data from 253 subjects (6 measures à two days, resulting in 3036 data points), associating positive childhood touch experiences with more favorable daily emotional states in adulthood. Specifically, individuals reported lower levels of stress, anxiety, loneliness, and burden related to the COVID-19 pandemic, along with increased happiness. Similarly, current intimate touch was linked to lower stress, pandemic-related burden, reduced loneliness, higher happiness, and moderately higher salivary oxytocin levels. Moreover, both childhood touch experiences and attitudes toward intimate touch significantly moderated the relationship between daily affectionate touch reports and individuals’ happiness, stress levels, pandemic-related burden, and cortisol concentrations. Our results emphasize the developmental importance of early touch experiences and highlight the lasting impact of both early and ongoing touch on attachment, social relationships, psychological well-being, and hormonal responses in everyday life.
Gesehen am 08.01.2025